2015
DOI: 10.1016/j.eats.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The Double-Pulley Anatomic Technique for Type II SLAP Lesion Repair

Abstract: The annual incidence and number of repairs of SLAP lesions in the United States are constantly increasing. Surgical repairs of type II SLAP lesions have overall good success rates. However, a low satisfaction rate and low rate of return to preinjury level of play remain a challenge with elite overhead and throwing athletes. Recent anatomic studies suggest that current surgical techniques over-tension the biceps anchor and the superior labrum. These studies suggest that restoration of the normal anatomy will im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Anchor line strength significantly exceeds the general suture; Sasaki et al [17] by comparing the mechanical characteristics of the screws and the anchor lines, it is found that there is no obvious statistical difference in the strength of the two lines, thus ensuring the early functional exercise after the operation. Suture anchor and double-pulley technique are widely used in shoulder surgery, such as bone Bankart injury, remplissage repair of shoulder instability, rotator cuff injury, and SLAP injury [18,19]. It can provide a repair effect in a large range as well as provide a stable internal fixation effect.…”
Section: Discussionmentioning
confidence: 99%
“…Anchor line strength significantly exceeds the general suture; Sasaki et al [17] by comparing the mechanical characteristics of the screws and the anchor lines, it is found that there is no obvious statistical difference in the strength of the two lines, thus ensuring the early functional exercise after the operation. Suture anchor and double-pulley technique are widely used in shoulder surgery, such as bone Bankart injury, remplissage repair of shoulder instability, rotator cuff injury, and SLAP injury [18,19]. It can provide a repair effect in a large range as well as provide a stable internal fixation effect.…”
Section: Discussionmentioning
confidence: 99%
“…The technique used in this study has been previously described in detail and has not changed since its original publication. 22 The double-pulley configuration provides a horizontal repair with large biceps–bone footprint, which improves healing and hopefully avoids strangulation of the superior labrum. 22 , 23 …”
Section: Methodsmentioning
confidence: 99%
“… 22 The double-pulley configuration provides a horizontal repair with large biceps–bone footprint, which improves healing and hopefully avoids strangulation of the superior labrum. 22 , 23 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations